The Mitochondrial Complexome of Medicago truncatula - Kiirika, Leonard M.; Behrens, Christof; Braun, Hans-Peter; Colditz, Frank (Frontiers in Plant Science, 2013)
Legumes (Fabaceae, Leguminosae) are unique in their ability to carry out an elaborate endosymbiotic nitrogen fixation process with rhizobia proteobacteria. The symbiotic nitrogen fixation enables the host plants to grow almost independently of any other nitrogen source. Establishment of symbiosis requires adaptations of the host cellular metabolism, here foremost of the energy metabolism mainly taking place in mitochondria. Since the early 1990s, the galegoid legume Medicago truncatula Gaertn. is a well-established model for studying legume biology, but little is known about the protein complement of mitochondria from this species. An initial characterization of the mitochondrial proteome of M. truncatula (Jemalong A17) was published recently. In the frame of this study, mitochondrial protein complexes were characterized using 2D BN / SDS PAGE. From 139 detected spots, the "first hit" (= most abundant) proteins of 59 spots were identified by mass spectrometry. Here, we present a comprehensive analysis of the mitochondrial “complexome” (the “protein complex proteome”) of M. truncatula via 2D BN / SDS PAGE in combination with high sensitive MS protein identification. In total, 1,485 proteins were identified within 158 gel spots, representing 467 unique proteins. Data evaluation by the novel GelMap annotation tool allowed recognition of protein complexes of low abundance. Overall, at least 36 mitochondrial protein complexes were found. To our knowledge several of these complexes were described for the first time in Medicago. The data set is accessible under http://www.gelmap.de/medicago/. The mitochondrial protein complex proteomes of Arabidopsis (available at http://www.gelmap.de/arabidopsis/) and Medicago are compared.